2013
DOI: 10.1111/jonm.12126
|View full text |Cite
|
Sign up to set email alerts
|

Job rotation and internal marketing for increased job satisfaction and organisational commitment in hospital nursing staff

Abstract: Job rotation and internal marketing help nursing personnel acquire knowledge, skills and insights while simultaneously improving their job satisfaction and organisational commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 31 publications
3
32
0
4
Order By: Relevance
“…Our study supports that job rotation created more knowledgeable nurses with a higher skill level (Chen et al, ; Järvi & Uusitalo, ; Jaturanonda et al, ; Mohan & Gomathi, ). Moreover, we also found job rotation to create recognition of peers (Pinhatti, ), increased influence and gave insight into peaks throughout the day while opening a way to communicate curiosity, questions or frustrations in relation to “the other ward.”…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study supports that job rotation created more knowledgeable nurses with a higher skill level (Chen et al, ; Järvi & Uusitalo, ; Jaturanonda et al, ; Mohan & Gomathi, ). Moreover, we also found job rotation to create recognition of peers (Pinhatti, ), increased influence and gave insight into peaks throughout the day while opening a way to communicate curiosity, questions or frustrations in relation to “the other ward.”…”
Section: Discussionsupporting
confidence: 87%
“…Studies have found positive effects of job rotation regarding personal experience, development and growth, improved motivation, knowledge and skills, broader insight into organisation and recognition of peers, a positive impact on job satisfaction, cultivation of collegial relations and enhanced career possibilities (Chen et al, ; Dinis & Fronteira, ; Ho et al, ; Järvi & Uusitalo, ; Mohan & Gomathi, ; Pan et al, ; Pinhatti, ). Two studies found negative consequences of a job rotation via focus groups or open‐ended questions.…”
Section: Introductionmentioning
confidence: 99%
“…Shift work characteristics were significantly different in the context of the QNWL, work design and work context of nurses who worked full‐time and rotated shifts. Rotating shift within fixed work schedules is important to maintain a balance in work‐sitting (Venkataraman, Anbazhagan, & Anbazhagan, ) and to increase work satisfaction and commitment (Chen, Wu, Chang, & Lin, ). Surprisingly, working in specialty units had a significant effect on QNWL, work design and work context.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis support the findings of the studies in the literature. The studies in the hotel sector (Hwang andChi, 2005 andGounaris, 2008), hospitals and medical centers (Chang and Chang, 2007;Iliopoulos and Priporas, 2011;Ahmad and Al-Borie ,2012;Pantouvakis, 2012;Dahl and Peltier, 2014and Chen et al 2015, Atlay Işık and Altunoğlu,2016b, education sector (Demir et al 2008;Usta, 2009;Başaran et al 2011);Ting, 2011;Hung, 2012;Ogunnaike et al 2012; Omar Salem, Kameswari and Rajyalakshmi, 2012;Barzoki and Ghujali, 2013;and De Bruin-Reynolds et al 2015) and sport schools and centers (Yıldız, 2011 andChiu et al 2014) have found similar results related to internal marketing activities and job satisfaction of employees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%